Manfort, a blend from plant extracts used for infertility treatment and improvement of testicular histology - Hussein, Mahmoud Elnahas (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Flavonoids and polyphenols are groups of natural substances have variable phenolic configurations, many benefits as anti-inflammatory and anti-oxidants, and have many protective roles against male reproductive system disorders. Objective of this study was to study the safety as well as the efficacy of a blend from some plants extracts with precise ratios and rich with flavonoids and polyphenols named in this study as “Manfort” on the safety, fertility, and testicular histology in the male mice. Methods: Firstly, some mice were used to evaluate the safety of Manfort and the levels of the testosterone in the serum of the treated animals with Manfort using biochemical analysis. Also, the efficacy of the Manfort on the histological architectures of the treated testis was evaluated using histological techniques. Results: The mice treated with Manfort did not show any signs of mortality, toxicities and blood contents changes. Furthermore, testosterone levels in the serum elevated after administration with Manfort twice a day for 21 days compared with the non-treated mice. Additionally, the histological structures of the testis improved in the mice treated with Manfort compared with that in the non-treated animals. Conclusions: In general flavonoids and polyphenols, which were found in the Manfort diet in a large amount, have important role in as antioxidant, anti-inflammatory and improve the fertility in the male mice. In the future these data might be very important to manufacture a drug composed from safe natural products for infertility and intractable diseases treatment.